TRANSFORMING UNIVERSITY ACADEMIC LITERACY THROUGH TRANSLANGUAGING PROJECT-BASED LEARNING IN ENGLISH AND INDONESIAN - Nanda Dwi Astri; Nurainun Hasibuan; Gumarpi Rahis Pasaribu (PT Rahis Cendekia Indonesia, 2026)
Multilingual university students are expected to produce academically credible texts in both English and Indonesian, yet language instruction often separates the two languages and treats students’ first-language resources as interference. This conceptual article develops a translanguaging-based project-based learning framework for strengthening university academic literacy. An integrative review and pedagogical design synthesis were conducted using recent peer-reviewed studies on translanguaging, project-based learning, academic writing, feedback, and Indonesian higher education, while retaining seminal academic-literacies sources. The synthesis generated five design principles: purposeful bilingual task architecture, authentic knowledge-building projects, staged movement across languages and modes, dialogic feedback, and dual-focused assessment of disciplinary meaning and language development. The proposed eight-week cycle guides students from multilingual inquiry and source mapping to bilingual planning, audience-specific drafting, peer review, revision, public dissemination, and metalinguistic reflection. The framework positions Indonesian as a cognitive and epistemic resource while maintaining explicit English-development goals. It offers a context-sensitive alternative to English-only instruction and a practical basis for future classroom experimentation in Indonesian universities.